Envisioning Critical Literacy through Literary Work for EFL Pre-Service Teachers - Rahmat Setiawan; Armelia Nungki Nurbani (J-SHMIC : Journal of English for Academic, 2023)
Teaching English seems to discredit literary works status as learning media, even though it has the inherent vigor to increase critical literacy. This is the fundamental case this research envisages to explore how literature as a bridge for critical literacy in the perspective of EFL pre-service teachers. Theoretically, this research is based on the concepts of literature, literacy, critical thinking, and EFL pre-service teachers. This research is a qualitative research. The approach used is a case study. The data in this study are responses or statements taken from several English education students who are EFL pre-service teachers. Data were taken from a discussion forum with 3 pre-service teachers as subjects. They are 7th semester students of English Language Education study program from 3 private universities in Surabaya. The technique of data is forum group discussion. The technique of data analysis is content analysis. From the analysis of the data, it results that the EFL pre-service teachers think that literary works are crucial to take portion because it can enhance the level of critical literacy through critical thinking, creativity, and open-mindedness.